Effect of Solvency, Liquidity, and Asset Quality on Stock Returns: Moderating Role of Independent Commissioners - Dea Lonita Manulang; Fahmi Natigor Nasution; Erlina Erlina (International Forum of Researchers and Lecturers, 2026)
Stock returns are a key indicator in assessing market perceptions of a company's performance and future prospects, particularly in the banking sector, which plays a strategic role in maintaining economic stability. However, inconsistent empirical findings regarding the impact of fundamental factors on banking stock returns highlight the need for further research, especially in cross-country contexts. This study examines the effects of solvency, liquidity, and asset quality on stock returns, with independent commissioners as a moderating variable, in banking sub-sector companies listed on the Indonesia Stock Exchange and the Vietnam Stock Exchange during 2022–2024. This research employs a quantitative approach using panel data regression and Moderated Regression Analysis (MRA) processed with EViews 12. The sample was selected through purposive sampling, consisting of 46 banks (138 observations) from Indonesia and 20 banks (60 observations) from Vietnam. The findings reveal that for banks listed on the Indonesia Stock Exchange, solvency, liquidity, and asset quality have no significant effect on stock returns, and independent commissioners do not moderate these relationships. In contrast, for banks listed on the Vietnam Stock Exchange, solvency positively affects stock returns, liquidity shows no significant effect, and asset quality negatively affects stock returns. Moreover, independent commissioners strengthen the relationship between solvency and stock returns but do not moderate the effects of liquidity and asset quality. These results indicate differences in fundamental characteristics and governance effectiveness between Indonesian and Vietnamese banks.